SKILLS REQUIREMENTS FOR QUANTITY SURVEYORS’ COMPETENCIES IN COST MANAGEMENT OF MECHANICAL AND ELECTRICAL SERVICES - Arowoiya, Victor; Akinradewo, Olusola (Journal of Surveying, Construction and Property, 2022)
Skills are abilities that are being possessed by a person to perform well in a specified job. This can be acquired or developed through training or experience in the field. The study is aimed at assessing skills needed by Quantity surveyors (QSs) in cost management of Mechanical and Electrical (M&E) services so that competency level can be improved. The quantitative research method was adopted for this study and the questionnaires were sent to experts in M&E services in the study area. Snowballing and purposive sampling techniques were used in selecting those experts. Bar chart, Mean Item Score, Gap analysis, Spearman correlation, Kruskal Wallis test was used in analyzing the retrieved data. The most important rated skills are Quantification, Valuation, Numerical, Critical thinking, and Documentation. QSs perform better in generic skills to technical skills where numerical, documentation and communication were rated highest. Gap analysis revealed that the possessed level of skills is less compare to the expected except in communication and computer skills. The findings revealed that there is a moderate relationship between the importance and performance of QSs in those skills. The results showed that there were ten out of eighteen skills with no significant difference while the other eight has a significant difference in the opinions of professionals. The study concluded that skills are very important to improve the competency level of any profession, especially in M&E services. It is therefore recommended that QSs should not shun continuous training like symposium, workshops and seminars to keep themselves abreast of how well to manage M&E services and also to further improve themselves in less performed skills. These had a wide gap between the importance and the performance rating.